2022
DOI: 10.1088/2053-1583/ac6cf3
|View full text |Cite
|
Sign up to set email alerts
|

International interlaboratory comparison of Raman spectroscopic analysis of CVD-grown graphene

Abstract: There is a pressing need for reliable, reproducible and accurate measurements of graphene’s properties, through international standards, to facilitate industrial growth. However, trustworthy and verified standards require rigorous metrological studies, determining, quantifying and reducing the sources of measurement uncertainty. Towards this effort, we report the procedure and the results of an international interlaboratory comparison (ILC) study, conducted under Versailles Project on Advanced Materials and St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 83 publications
(122 reference statements)
0
12
0
Order By: Relevance
“…These parameters are as follows: (1) the number of mass loss steps, (2) thermal stability, (3) temperature of maximum mass change rate ( T p ) for each decomposition step, (4) the mass contents (%) of moisture, oxygen groups, carbon, combustible organic impurities, and (5) the mass content (%) of noncombustible residues. These parameters have been selected to combine the measurement of physical and qualitative and quantitative chemical properties of GR2Ms based on their practical relevance, complementarity with other ISO characterization methods and the developed procedures from both the authors and the literature. , …”
Section: Introductionmentioning
confidence: 99%
“…These parameters are as follows: (1) the number of mass loss steps, (2) thermal stability, (3) temperature of maximum mass change rate ( T p ) for each decomposition step, (4) the mass contents (%) of moisture, oxygen groups, carbon, combustible organic impurities, and (5) the mass content (%) of noncombustible residues. These parameters have been selected to combine the measurement of physical and qualitative and quantitative chemical properties of GR2Ms based on their practical relevance, complementarity with other ISO characterization methods and the developed procedures from both the authors and the literature. , …”
Section: Introductionmentioning
confidence: 99%
“…A recent interlaboratory study has concluded that the standard deviation of peak widths of graphene spectra, especially for the 2D band, are substantially reduced if Voigt fitting is used instead of Lorentzian. 68 A Voigt function is a convolution of a Gaussian and a Lorentzian function and it captures better the broadening of the 2D mode resulting from doping, strain variations or increasing defect density since the gaussian component of the Voigt can accommodate the change in the peak tails. Therefore, we have developed an alternative code where Lorentzian fitting functions are replaced by a pseudo-Voigt functions as defined in OriginPro 2020 (‘ PsdVoigt1 ’):where y 0 is a constant background, A is the peak area, w is the FWHM, x 0 is the peak center and m u the profile shape-parameter (or gaussian weight/fraction).…”
Section: Methodsmentioning
confidence: 99%
“…Instruments 2023, 7, 30 2 of 16 These advantages made Raman spectroscopy a tool used in numerous fields, both in research and technology [5]. Speaking of areas such as the pharmaceutical industry [2], medicine [6,7], analytical chemistry [8][9][10][11], mineralogy [12,13], materials science [14], historical research [9,15], and even forensic science [16], it has revealed many applications. It is easy to see the importance of this technique, but is it suitable for its wide use in highly regulated environments?…”
Section: Introductionmentioning
confidence: 99%